A survey on the prevalence of apathy in elderly people referred to specialized memory centers - Manera, Valeria; Fabre, Roxane; Stella, Florindo [UNESP]; Loureiro, Júlia Cunha [UNESP]; Agüera-Ortiz, Luis; López-Álvarez, Jorge; Hanon, Cécile; Hoertel, Nicolas; Aalten, Pauline; Ramakers, Inez; Zeghari, Radia; Robert, Philippe (Wiley, 2019)
Background: Apathy is a pervasive neuropsychiatric syndrome in people with neurocognitive and psychiatric disorders. The diagnostic criteria for apathy (DCA) have been revised in 2018. Objectives: Employing the 2018 DCA, in the present study, we investigated in groups of elderly subjects suffering from different neuropsychiatric disorders (a) the apathy prevalence; (b) the most commonly affected apathy dimensions (behavior/cognition, emotion, and social interaction); (c) the sensitivity and specificity of those dimensions for apathy diagnosis; and (d) the concurrent validity of 2018 DCA compared with the 2009 DCA. Methods: This multicenter survey included 166 subjects. Each center checked the presence of apathy in subjects belonging to the following DSM-5 diagnoses: mild neurocognitive disorders (mild NCDs); major NCDs; affective disorders (Aff D); and subjective cognitive decline (SCD). Results: The frequency of apathy varied significantly based on the diagnostic groups (0% of subjects with apathy in the SCD group; 25% in the mild NCD group; 77% in the major NCD group; and 57% in the Aff. D group). All subjects with apathy fulfilled the criteria for the behavior/cognition dimension, 73.1% fulfilled the criteria for the emotion dimension, and 97.4% fulfilled the criteria for the social interaction dimension. Behavior/cognition showed the highest sensitivity, the copresence of emotion and social interaction the highest specificity. The concordance between the 2009 and the 2018 DCA indicated an almost perfect agreement. Conclusions: These results are consistent with previous reports and confirm that the social interaction dimension added to the 2018 DCA is present in most of subjects with apathy referred to specialized memory centers.
Keywords: affective disorders; apathy; diagnostic criteria; elderly; neurocognitive disorders; psychiatric disorders; subjective cognitive decline